Hubungan Pola Makan Dan Aktivitas Fisik Dengan Kejadian Obesitas Pada Remaja Di SMA Negeri 1 Kontunaga - La Ode Liaumin Azim (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Obesity among adolescents is a growing health problem in Indonesia, especially among adolescents aged 6-12 years, which was 19.7% in 2023. Unhealthy eating patterns and lack of physical activity are the main factors that can influence the incidence of obesity. This study aims to analyze the relationship between eating patterns, physical activity, and the incidence of obesity among adolescents at SMA Negeri 1 Abuki. This study used a quantitative method with a cross-sectional approach. The population in this study consisted of 82 adolescent students. The sample used in this study consisted of 41 people selected using simple random sampling. The data were obtained from direct interviews in the field using questionnaires and measurements, and the measurement results were processed using SPSS 25 For Windows. The data were then analyzed using univariate and bivariate analyses using the Chi-Square statistical test. Based on the results of the chi-square statistical test on the eating pattern variable, a p-value of 0.000 was obtained, which is less than 0.05 (0.000 < 0.05). Meanwhile, the results of the chi-square statistical test on the physical activity variable obtained a p-value of 0.000, which is less than 0.05 (0.000 < 0.05). Unhealthy eating patterns and lack of physical activity are the main risk factors for obesity among adolescents at SMA Negeri 1 Abuki. This study suggests the need for intervention in the form of health education to improve